CLIPPERS Spectrum Disorder: A Rare Pediatric Neuroinflammatory Condition. (7th March 2019) - Nemani, Tarishi; Udwadia-Hegde, Anaita; Keni Karnavat, Purva; Kashikar, Ritu; Epari, Shridhar
CLIPPERS (chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) is a recently described, rare neuroinflammatory disorder diagnosed by clinical symptoms involving the brain stem with a distinct pattern on neuroimaging and a perivascular T-lymphocyte infiltrate on brain biopsy. It is a condition usually described in adults in the fourth to fifth decade. We report a case of 13-year-old Indian boy who presented with recurrent episodes of ataxia and diplopia with onset at 7 years of age. He was investigated extensively to rule out infective, neoplastic, autoimmune, and demyelinating conditions over a span of 6 years. The diagnosis of CLIPPERS was entertained on the basis of clinico-radio-pathological correlation. Treatment with steroids and steroid-sparing agents, particularly methotrexate, seems to provide a promising outcome. With very few cases in literature so far, reporting of a larger case series with pediatric onset may expand it to CLIPPERS spectrum disorder.